(untitled) (Damascus University Journal of agriculture sciences, 2022)
This research was conducted at the Central Grain Laboratory and laboratories of the Department of Food Sciences, Faculty of Agriculture, Damascus University, during the period from August 2019 to March 2020, with the aim of optimizing the process of local soft wheat kernels conditioning in order to yield the best milling performance and flour quality properties. The Syrian soft wheat variety Cham8 (Triticum aestivum) was selected for this study, and was obtained from the Central Grain Laboratory, the grains were conditioned to final moisture contents (14, 15 and 16%) and tempering times (8, 16 and 24 hours) for each degree of moisture. The indicators of grain milling were studied in terms of flour weight and flour extraction rate, and the physiochemical properties of the flour samples obtained from milling of the conditioned grains were analyzed. Results of the milling performance analysis showed significant reduction in flour weight and flour extraction rate as the final moisture content and tempering period increased, where the extraction rate decreased by approximately 1.78% for every 1% water added. This accompanied with improvement in flour quality, where ash content and flour colour decreased. On the other hand, conditioning parameters did not reveal high significant effects on gluten quality and quantity. Final moisture content revealed the dominant effect on milling performance parameters and flour physiochemical properties according to the F test and variance distribution test, where (98.72%, 95.00%, 89.69%, 83.02% and 66.99%) of the variance of flour extraction rate, ash content, the color degree, wet gluten and dry gluten contents, respectively, were due to final moisture content, while it decreased to (16.21%) for the gluten index, which was affected (33.19%) by the variable tempering period, and (50.60%) by the interaction effect of the final moisture content and the tempering period. On the other hand, optimization of wheat conditioning process demonstrated that tempering soft wheat to 15% moisture content for 16 hours yielded the best milling performance and flour quality properties